2020
DOI: 10.31219/osf.io/p7ex8
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High-dose intravenous vitamin C treatment for COVID-19

Abstract: COVID-19 pneumonia seems to be a lung injury caused by the hyperactivation immune effector cells. High-dose vitamin C may result in immunosuppression at the level of these effectors. Therefore, intravenous high-dose vitamin C could be safe and beneficial choice of treatment in the early stages of COVID-19.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
46
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 15 publications
0
46
0
8
Order By: Relevance
“…However, new knowledge regarding the pharmacokinetic properties of Vit-C, and recent preclinical studies, have revived interest in the utilization of high-dose Vit-C for cancer treatment [132][133][134][135][136][137][138][139][140][141][142][143][144][145]. Similar is the case of using IV Vit-C as antiviral, especially for the recent Covid19 [146][147][148][149][150]. It is believed that IV Vit-C has been particularly effective by inhibiting the production of cytokines storm due to Corvid19.…”
Section: Discussionmentioning
confidence: 99%
“…However, new knowledge regarding the pharmacokinetic properties of Vit-C, and recent preclinical studies, have revived interest in the utilization of high-dose Vit-C for cancer treatment [132][133][134][135][136][137][138][139][140][141][142][143][144][145]. Similar is the case of using IV Vit-C as antiviral, especially for the recent Covid19 [146][147][148][149][150]. It is believed that IV Vit-C has been particularly effective by inhibiting the production of cytokines storm due to Corvid19.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin C has also been evoked for use in cases of SARS-CoV-2 infection, since at high doses it could result in the immunosuppression of hyperactivation immune effector cells that cause lung injury in COVID-19 cases, while being a safe treatment option [56].…”
Section: Developing Drugsmentioning
confidence: 99%
“…Cai et al showed that vitamin C can improve the outcome in pneumonia due to in uenza virus by its effect on inhibition of CORT synthesis which reduces the susceptibility to in uenza viral infection 20 . Regarding critically ill COVID-19 patients with pneumonia with a high mortality rate, it seems that timely administration of high dose intravenous vitamin C has been particularly effective by inhibiting the production of cytokines storm due to COVID-19 21 .…”
Section: Discussionmentioning
confidence: 99%